Reducing Production Lead Time Through Value Stream Mapping - Esfandyari, Alireza (2008)

(untitled)
This research addresses the application of lean manufacturing concepts to the discrete production sector of a metal fabrication company in Malaysia. The goal of this research was to investigate the application of lean manufacturing tools to reduce production lead time for a dedicated product family. This study is applied to a small metal-based manufacturing company (referred to as ABC). Root-cause analysis based on behavioral and informational factors was developed for seven waste indicators to identify the waste in managerial-level stage. Value Stream Mapping (VSM) is prescribed as part of the lean production portfolio of tools and has been applied in a variety of industries to identify lean tools to try to eliminate the waste. VSM was used to first map the current state in order to realize the current production lead time and to identify sources of wastes at the worker-level stage. Then a future state map was developed using lean tools and techniques and answering the eight questions stated by Rother and Shook (1999). The future state map identifies the reduced production lead time based on lean concept. Two detailed simulation models using system modeling corporation’s Arena 7 package was developed. The current state simulation verifies the current production lead time from current state map and the future state simulation which was developed based on the future state map quantifies reduction of production lead time. It is concluded that using Value Stream Mapping (VSM), the production lead time of 200 units of ‘back plate indoor’ reduced from less than 15 days in current state map to less than 9 days in future state map. Also, the simulation shows that production lead time reduction to eight days could be accomplished at ABC if lean tools are utilized. Comparing the production lead time of eight days in simulated model and less than nine days in Value Stream Mapping (VSM) showed that VSM is a reliable tool for production schedule and estimating production lead time in lean production system.